GAMBARAN SISA KLOR DAN MPN COLIFORM JARINGAN DISTRIBUSI AIR PDAM - Hermiyanti, Pratiwi; Wulandari, Endang Tri (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
PDAM water that has a long distance from the reservoir almost does not smell chlorine so it is possible less than the quality standards can cause the bacteria in the water distribution of PDAM. Purpose of this research to know residual content of chlorine and MPN coliform on PDAM water distribution of Surabaya city 2017. The type of research is observational analytic with cross sectional design. The sampling procedure was performed at 4 locations with replication 3 times morning and daytime. Examination of chlorine residual content using comparator test kit, MPN coliform in laboratory, while pH, water temperature and air temperature is done in the field. Data were analyzed by multiple linear regression test presented in tabular form and analyzed and compared with standard quality standard. The results of the average residual chlorine morning 0,57 mg / l and daytime 0,5 mg / l, have fulfilled the standard of quality of residual chlorine waste water content that is 0,2-1,0 mg / l. The average MPN coliform in the morning was 8.5 colonies / 100 ml of sample and the daytime was 10.7 colonies / 100 ml of sample, so during the day the sample did not meet the standard quality of MPN coliform of piping water for 10 colonies / 100 ml samples. Average morning pH 7.7 and daytime 7.8, morning water temperature 26.8°C and daytime 27.7°C and morning air temperature 27.7°C and daytime 30,3°C. The conclusion obtained is the distribution distance affect the residual chlorine content and MPN coliform (p <0,05). Suggestion for PDAM is need to be done chlorine addition to active chlorine at furthest point that is 9 kilometers can fulfill requirement.